Hydatid Disease of The Brain Parenchyma: A Systematic Review - Fattah H. Fattah; Azad Star Hattam; Zana Omar kak Abdullah; Khanda A. Anwar; Rezhen J. Rashid; Abdullah K. Ghafour; Alaa B. Latif; Hiwa O. Abdullah; Sasan M. Ahmed; Abdullah Dler Ahmad (Barw Medical Journal, 2025)
AbstarctIntroductionIsolated brain hydatid disease (BHD) is an extremely rare form of echinococcosis. A prompt and timely diagnosis is a crucial step in disease management. This study is a systematic review of studies on intra-parenchymal BHD.MethodsStudies that had the following properties were included: 1) The intra-parenchymal brain infection had been confirmed by diagnostic modalities, surgical findings, or histopathology. 2) The patient details were provided in the study. 3) The cystic lesion [s] were located intracranially.ResultsAltogether, 112 studies with a sample size of 178 cases met the inclusion criteria. Males (60.1%) showed a higher prevalence of the disease than females (38.2%). Most of the cases (64%) were affected during the first and second decades of their lives. Left-side multi-lobe involvement was the most common type of involvement (28.1%), followed by right-side multi-lobe involvement (26.4%). Surgery was the primary treatment option (97.2%), with the Dowling technique or the modified Arana-Iniguez method as the preferred approach. The total recurrence and mortality rates were 7.3% and 3.4%, respectively.ConclusionThe definitive treatment for BHD is surgery, with the aim of removing cysts intact or excising mass lesions completely. A history of cyst rupture during operation may increase the likelihood of recurrence, and an extensive follow-up is required.IntroductionHydatid disease (HD) is a parasitic infection caused by the larvae of the tapeworm Echinococcus. Different genera of this microorganism can cause disease; however, in humans, two species have major clinical sequelae. Echinococcus granulosus results in cystic disease, the most common type, while Echinococcus multilocularis causes alveolar echinococcosis (AE), presenting as a mass or cystic lesion. The latter form of the disease is more invasive and aggressive, accompanied by numerous diagnostic and management challenges [1-3]. The most common organs affected by hydatidosis are the liver and lungs. However, other parts of the body can also be affected, including the bones, pericardium, orbits, ovaries, central nervous system (CNS), and other organs. In the literature, 2–3% of cases show involvement of the CNS. The incidence of isolated brain involvement is reported to be 1–2% of all cases of echinococcosis, representing approximately 2% of all intracranial space-occupying lesions [4-6]. Brain hydatid disease (BHD) is endemic in many regions where livestock raising is prevalent, and human-animal contact is common. The incidence varies geographically, with higher rates reported in rural areas. However, globalization and increased travel have led to sporadic cases being reported in non-endemic regions as well. Humans can become infected through the ingestion of parasite eggs in contaminated food, water, or by direct contact with infected dogs, canines, and sheep [7,8]. Most cases of intracerebral echinococcosis are diagnosed in pediatrics (50-75%) [9]. The clinical presentation of hydatidosis depends on the patient's age, the size, number, and location of the cyst, as well as the host's immune system. Patients with HD can remain asymptomatic for long periods, as the lesions take years to develop. When they grow well, intracranial hypertension secondary to the mass effect on the surrounding tissues is usually the first clinical sign of brain involvement. The disease may not cause focal neurological signs until they become enlarged [10-12]. In the literature, several reviews have been published on cerebral HD; however, there is a scarcity of systematic reviews on the topic. This study is a systematic review of studies on intra-parenchymal BHD published over the last two decades [1-112].MethodsStudy design and reporting standardsThe study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.Search strategyA systematic review of all published studies on brain parenchymal HD was conducted from 2000 to 2024 using the following databases: Google Scholar, PubMed/MEDLINE, Cochrane Library, Science Direct, and EMBASE. The keywords used in the search included:[brain OR intraparenchymal OR cerebral OR intracerebral OR cerebrum] AND [hydatid OR hydatidosis OR echinococcoses OR echinococcosis OR echinococcal OR echinococcus].Eligibility criteriaNon-English language studies and those unrelated to humans were excluded before or during the initial screening. Studies of BHD were included if: 1) Diagnostic modalities, surgical findings, or histopathology confirmed the intraparenchymal brain infection. 2) Patient details were provided in the study. 3) Studies published in predatory journals (inappropriately peer-reviewed) and those not meeting inclusion criteria were excluded [113].Study selectionTitles and abstracts of identified studies were initially screened, followed by full-text screening to assess eligibility.Data extractionData extracted from eligible studies included study design, country of study, patient age, gender, residency, symptoms, medical history of HD, cyst characteristics, diagnosis, management, follow-up, and outcomes.Data analysisData were analyzed qualitatively (descriptive analysis) using the Statistical Package for the Social Sciences (SPSS) version 27.0 softwareResultsIn total, 318 studies were obtained from the resources. Before any screening, 38 of them were directly excluded due to duplication, non-English language, non-articles, and animal studies. Following the initial screening, 92 studies did not meet the inclusion criteria and were excluded. The remaining 188 studies underwent full-text screening, and 122 of them were assessed for eligibility. Ultimately, 112 studies (comprising 178 cases) met the inclusion criteria (Figure 1). The characteristics of the included studies are shown in Table 1. Out of these studies, 101 (90.2%) were case reports, 10 (8.9%) were case series, and one (0.9%) was a retrospective cohort study. Most of the cases were reported in Turkey (24.1%), followed by Iran (16.7%), India (15.2%), and Morocco (9.8%). Males (60.1%) showed a higher prevalence of the disease than females (38.2%). Most of the cases (64%) occurred in the first and second decades of life, with a mean age of 20.44 ± 16.76 years. There were 71 cases (39. 9%) in rural areas and eight cases (4.5%) in urban areas. The residency of the remaining 99 cases (55.6%) was not reported. The type of the disease was cystic in 158 cases (88.8%) and alveolar in 20 cases (11.2%). Thirteen (7.3%) cases had a previous history of HD. The most commonly presented symptoms were signs of raised intracranial pressure, including headache (62.9%), vomiting (43.3%), followed by seizure (30.3%) and paresis (28.7%). Multiple organ involvement was present in 48 (27%) cases, involving the lung, liver, kidney, adrenal gland, blood vessels, or bones. The disease was primary with a single cyst or lesion in 118 patients (66.3%), primary with multiple cysts in 27 (15.1%), secondary with a single cyst in 23 (13%), and secondary with multiple cysts in 10 (5.6%). Left-side multi-lobe involvement was the most common type of involvement (28.1%), followed by right-side multi-lobe involvement (926.4%) and parietal lobe involvement (18.5%).Serology had been done in 55 cases (30.9%), and it was positive in 34 (19.1%). Computed tomography scans (CT) or magnetic resonance imaging (MRI) were used in all cases. Surgery was the main treatment option (97.2%). The Dowling technique, or modified Arana-Iniguez, was the method of choice (95.5%). Surgery in three cases (1.7%) was done through the Burr-hole technique instead of open craniotomy. Conservative management was performed in five cases (2.8%). The patients underwent follow-up with a mean interval of one year. Recurrence was reported in 13 cases (7.3%). Among those, six cases (46.1 %) had intra-operative complications of traumatic rupture of the cyst, and two cases (15.4 %) had a surgical puncture of the cyst. The remaining five cases (38.5%) did not experience any intraoperative complications. The mortality rate was 3.4% (Table 2).Table 1. Raw data of the included studies.AuthorCountryStudy designNoAgeSexPresenting symptomsImagingISHCNo. of cyst [s] in brainLocation of cyst [s] in brainSize [cm]SerologyType of managementPre-Op complicationIntra-Op complicationPost-Op complicationAdjuvant therapyFollow up* outcomeSvrckova et al [1]United Kingdom Case report 330MHeadache, seizureMRIYes>1Right parietal, right temporalN/APositiveConservative [Albendazole/praziquantel/steroid/antiepileptic]N/AN/AN/A NoneImproved26MCollapse, slurred speech, seizure, left side hemiparesisCT, MRIYes1Right parietal and basal gangliaN/APositiveConservative [Albendazole/Praziquantel/steroid/Antiepileptic]N/AN/AN/ANoneImproved37MDry coughMRIYes>1Bilateral hemisphereN/APositiveConservative [Albendazole]N/AN/AN/ANoneImprovedAltibi et al [2]BrazilCase report113MHeadache, nauseaCT, MRIYes1Right parieto-occipital4.7NegativeSurgical removal [Dowling]/neuronavigationNoneNoneNoneN/AN/ACasulli et al [3]ItalyCase report1 6MRight side hemiparesisCT, MRIYes1Left fronto-parietal6.8NegativeSurgical removal/neuronavigationNoneNoneSeizure, headache, worsened right hemiparesis, peri-lesional edemaAlbendazole, Antiepileptic,SteroidImprovedLakhdar et al [4]MoroccoCase report130MHeadache, right side hemiparesisMRIYes>1Left fronto-parietalN/ANegativeSurgical removalNoneRupture of cystsNoneAlbendazole, Antibiotics, AntiepilepticRecoveredFariba Bi. [5]IranCase report118FHeadache, nausea, vomitingMRIYes1Right temporalN/AN/ASurgical removalNoneNoneNoneAlbendazole, anticonvulsantRecoveredSaleh et al [6]EgyptCase series 49MDrowsiness, vomiting, blurred vision, headacheCT, MRIYes>1Right parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A10MSeizureCT, MRIYes1Right frontalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A12MSeizureCT, MRIYes1Left fronto-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A14FHeadacheCT, MRIYes1Right parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/AAlomari et al [7]Saudi ArabiaCase report18FBilateral exophthalmos, blurred vision, headacheCTYes1Left frontal15.3 NegativeSurgical removal [Dowling]NoneNoneSeizureAlbendazoleRecoveredHafedh et al [8]IraqCase report127MSeizure, headache, left side hemiparesisCT, MRIYes1Right hemisphereN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedUmut et al [9]TurkeyCase report114MDouble vision, headache nausea, vomitingMRIYes2Left occipital lobe, right insula1st: 5.6 2nd:2.6NegativeSurgical removal [Dowling]first occipital cysts and after 6 m temporal insulaNoneNoneNoneAlbendazoleRecoveredÇavusoglu et al [10]IndiaCase report18FLeft side hemiparesis, left side mouth deviation, slurred speechCT, Contrast MRIYes1Left fronto-parietal10.2 N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/AGarg et al [11] IndiaCase report18FLeft side hemiparesis, left side mouth deviation, slurred speechCT, Contrast MRIYes1Left fronto-parietal10.2 N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A Raouzi et al [12]Morocco Case series 414MSeizureCT, MRIYes1Right parietal areaN/ANegativeSurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A4MHeadache, vomitingCT, MRIYes1Right fronto-parietal7.05PositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A3MSeizureCT, MRIYes1Right parietal lobeN/APositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A22FSeizureCT, MRIYes>1Left fronto-parietalN/ANegativeSurgical removal [Dowling]NoneNoneNoneAlbendazoleN/A Assefa et al. [13] EthiopiaCase series 48MHemiparesis, nausea and vomitingContrast CTYes1Left fronto-parietal + daughter cystN/AN/ASurgical RemovalNoneRupture of CystCystic abscess, peri-cystic vasogenic edemaN/ARecurrence5FHemiparesis, nausea and vomitingContrast CTYes1Right fronto-parietalN/AN/ASurgical RemovalNoneNoneNoneN/AN/A10FHemiparesis, nausea and vomitingContrast MRIYes1Right parietalN/AN/ASurgical RemovalNoneNoneNoneN/AN/A29MHemiparesis, nausea and vomitingContrast MRIYes1Right parietalN/AN/ASurgical RemovalNoneNoneNoneN/AN/ATanki et al [14] IndiaCase series910MSeizureCT, MRIYes1Right frontalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered12FHeadache, nausea, vomiting, hemiparesisCT, MRIYes>1Left parietalN/AN/ASurgical removal [Dowling]NoneRupture of CystN/AAlbendazoleRecurrence12MSeizure, headache, nausea, vomitingCT, MRIYes1Right parietalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered10MHeadache, nausea, vomitingCT, MRIYes1Left parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered11MSeizure, hemiparesisCT, MRIYes1Right parietalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered16FSeizureCT, MRIYes1Left frontalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered14MSeizure, hemiparesisCT, MRIYes>1Right parietalN/AN/ASurgical removal [Dowling]NoneRupture of CystN/AAlbendazoleRecurrence7FSeizureCT, MRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecovered12FSeizure, hemiparesisCT, MRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneNoneN/AAlbendazoleRecoveredNoori et al [15]IraqCase report126MHeadache, nausea, vomitingCTYes1Right temporo-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneN/AN/AHaradhan et al [16]BangladeshCase report114MHeadacheContrast CT, Contrast MRIYes1Right fronto-parietal12.48N/ASurgical removalNoneNoneRight frontoparietal subdural hygroma, hydrocephalus, pseudocystAlbendazoleN/APanda et al [17]IndiaCase report14MSeizureCT, MRIYes1Left fronto-parietal4.47N/ASurgical removal [Dowling]NoneRupture of CystNoneN/AN/ASharifi et al [18]IranCase report144MMood swings, restlessness, and headacheCTYes1Right frontoparietal lobeN/AN/ASurgical removalNoneNoneNoneAlbendazoleN/AAydin et al [19]TurkeyCase series29FHeadache, vomiting, bilateral decreased vision, left side tremor, left side hemiparesisCT, MRIYes1Right fronto-temporo-parietal9.81NegativeSurgical removal [cavity placed balloon/ Dowling]NoneNoneNoneN/AN/A18MHeadache, vomiting, blurred vision, fever, quadriparesisCT, MRIYes1Right fronto-temporo-parietal8.96NegativeSurgical removal [cavity placed balloon/ Dowling-Orlando]NoneNoneNoneN/ARecoveredÇakir et al [20]TurkeyCase report16MHeadacheMRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneCardiac arrest/deathN/AN/ADeathPonnambath et al [21]IndiaCase report140MHeadache, seizureContrast MRINo1Left occipital lobe3N/ASurgical removal/neuronavigationNoneNoneNoneAlbendazoleMinimal visual field defectİzgi et al [22]TurkeyCase report15MHeadache, nausea, vomiting, deviation of the eyesMRIYes1Right parietal lobe6.92N/ASurgical removal [Dowling]NoneNoneNoneN/AN/AEl Ouarradi et al [23]MoroccoCase report111MNausea, vomitingCTYes1Right fronto-parieto-temporal lobe9.75PositiveSurgical removal [Dowling]NoneShock/cardiac arrest/deathN/AN/ADeathBaboli et al [24]IranCase report119MHeadache, left hemiparesisContrast MRIYes1Right fronto-parietal lobe8PositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedArega et al [25]EthiopiaCase report18FHeadache, vomitingContrast MRIYes1Right temporal13.27N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredAltaş et al [26]TurkeyCase report126FHeadache, nausea, vomitingContrast CT, MRIYes1Right parieto-occipital7.95PositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleN/AMadeo et al [27]USACase report182FEmergency caseCT, MRIYes1Left hemisphere4.08PositiveConservative [Albendazole]N/AN/AN/ANoneStable cystMenschaert et al [28]MoroccoCase report15FSeizuresMRIYes1Left parietalN/APositiveSurgical removalNonePuncture of CystNoneAlbendazoleLearning disabilitiesŞule et al [29]TurkeyCase report183MHeadache, forgetfulnessContrast MRINo1Right frontal lobe4N/ASurgical removalNoneNoneNoneN/AN/ABenhayoune et al [30]MoroccoCase report118FHeadache, vomiting, seizureContrast MRINo1Right parieto-occipital7.9N/ASurgical removal [Arana]NoneNoneNoneAlbendazole, AntiepilepticRecoveredVikaset al [31]IndiaCase report120MSeizure, right side paresthesia, headache, vomitingContrast CT, contrast MRIYes>1Left fronto-parietalN/AN/ASurgical removalNoneNoneNoneAlbendazoleRecoveredReddy et al [32]IndiaCase report135FHeadache, vomiting, altered sensorium, loss of consciousnessContrast CTYes 5 Both parietal lobesN/AN/ASurgical removalNoneNoneNoneN/ARecoveredAl-Rawi et al [33] Iraq Case series 83.5FN/ACTYes1Left parietalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered7FN/ACTYes1Right parietalN/AN/ASurgical removalNoneRupture of CystDelayed recoveryAntiepilepticRecurrence11MN/ACTYes1Left fronto-parietalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered13FN/ACTYes1Right frontal lobeN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered15MN/ACTYes1Left fronto-parietalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered15MN/ACTYes1Right fronto-parietalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered35MN/ACTYes1Left fronto-parietalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered14FN/ACTYes1Left frontalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecoveredNaderzadeh et al [34]IranCase report 112MHeadache, nausea, vomiting, fever, decreased visionMRIYes1Left parieto-occipital4.56N/ASurgical removalNoneNoneVisual deficitAlbendazoleMyopia, occasional seizureShafiei et al [35] Iran Case series 33MHeadacheCTYes1Left temporo-parietal5.83N/ASurgical removalNoneNoneNoneAlbendazole, AntiepilepticRecovered59FHeadache, feverCTYes1Right parieto-occipital8.48N/ASurgical removalNoneNoneNoneAlbendazole, AntiepilepticRecovered53FAngiopathy, nausea, vomitingCTYes1Left fronto-occipitalN/AN/ASurgical removalNoneRupture of CystNoneAlbendazole, AntiepilepticRecurrenceNechi et al [36]TunisiaCase report150FSeizureCT, MRIYes1Right frontal lobe4.97N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredEkici et al [37]TurkeyCase report112MHeadache, vomiting, diplopiaCTYes>1Right parieto-occipitalN/ANegativeSurgical removal [Dowling]/neuronavigationNoneNoneNoneAlbendazoleRecoveredBagheri et al [38]IranCase report118MNausea,vomiting, right side hemiparesisCT, MRIYes1Left temporal6N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredBušić et al [39]CroatiaCase report137FHeadache, vomiting, balance difficulties, left side hemiparesisCT, MRIYes5 Right parietal lobeN/APositiveSurgical removalNoneNoneWound infection and osteomyelitisAlbendazoleRecurrenceNashibi et al. [40]IranCase report159MDisorientation, right side hemiparesis, headache, dysarthriaCT, MRIYes1Left parieto-temporalN/AN/ASurgical removal [Dowling]NoneNoneNoneN/AImprovedAmmor et al [41]MorroccoCase report14N/AWeakness, headache, vomitingContrast MRIYes1Right fronto-temporo-parietalN/AN/ASurgical removalNoneNoneNoneN/AHeadache, subdural hygromaAlok et al [42]SyriaCase report15FRight side hemiparesisCT, MRIYes1Pons2.1PositiveSurgical removal [Dowling-Orlando]NoneNoneNoneAlbendazoleImprovedChatzidakis et al [43]GreeceCase report127MQuadriparesis, headache, nausea, vomitingCT, MRIYes>1Bilateral frontal, bilateral occipital, cerebellumN/AN/ASurgical removal [3 times]NoneNoneGeneralized seizure post 1st OPAlbendazoleRecoveredPanagopoulos et al [44]GreeceCase report111MHeadache, vomitingContrast CT, contrast MRIYes1Right fronto-parietal6.85NegativeSurgical removal/neuronavigationNoneNoneNoneAlbendazoleImprovedKaraaslan et al [45]TurkeyCase report122MNausea,vomiting, headacheCT,MRIYes1Left parieto-occipital6.92N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredHajhouji et al [46]MoroccoCase report117FSeizureContrast MRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredTascu et al [47]RomaniaCase report13N/APost cranio-cerebral traumaContrast CT, MRIYes1Left fronto-parieto-occipital lobe10N/ASurgical removal [Arana]NoneNoneNoneN/ASubdural hematomaGhaemi et al [48]IranCase report128MHeadache, nausea, vomitingCT,MRINo1Right temporal6N/ASurgical removalNoneNoneNoneN/AN/AGanjeifar et al [49]IranCase report113MFever ,abdominal painCT, MRIYes1Left parieto-occipitalN/APositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredNemati et al [50]IranCase report16MAtaxia, left side hemiparesisCT,MRIYes1Right fronto-parietal13.29 NegativeSurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedMehrizi et al. [51]IranCase report15FHeadache, nausea, vomitingCTYes1Fronto-parietal10 N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredFakhouri et al [52]SyriaCase report15FHeadache, vomiting, difficult walkingCT, MRIYes1Right Cerebellum6 N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredGhasemi et al [53]IranCase report18FMalaise, vomiting, headacheCT, contrast MRIYes1Left temporo-parieto-occipitalN/ANegativeSurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredMallik et al. [54]India Case report2 10MHeadache, vomiting, right side hemiparesis, aphasiaMRIYes1Left temporo-parietal10.32 N/ASurgical removal [Dowling]NoneRupture of CystNoneAlbendazole, Antibiotics, Antiepileptic, SteroidsImproved16MDecreased vision, headache, vomitingCECTYes1Left fronto-temporo-parietalN/APositiveSurgical removal [Dowling]NoneRupture of CystNoneAlbendazoleSeizure, unconsciousnessArora et al[55]IndiaCase report19FSeizure, decreased vision, headache, vomitingCTYes1Left parietal lobe7.23PositiveSurgical removal [Dowling]NoneNoneNoneN/AN/AAl-Musawi et al [56]IraqCase report114FSeizureCTYes1Left parietalN/AN/ABurr-hole surgical removalDeterioration in the consciousness, right side hemiparesis, apneaNoneNoneAlbendazole, anticonvulsantRecoveredGhasem et ali [57]IranCase report130FSeizure, headache, intellectual impairment, abnormal behaviorCT, MRIYes1Left frontalN/AN/ASurgical removal [Dowling]NoneNoneNoneN/ARecoveredPolat et al. [58]TurkeyCase report145MPersonality disorder, nausea, vomitingCT, MRIYes1Left fronto-parietalN/APositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleRecurrence & DeathHmada et al [59] MoroccoCase report25FDecreased vision, tremorCTYes1Right fronto-temporo-parietalN/AN/ASurgical removal [Arana]NoneNoneNoneAlbendazole, AntiepilepticImproved5FRight side heavinessN/AYes1Right fronto-temporo-parietalN/AN/ASurgical removal [Arana]NoneNoneNoneAlbendazole, anticonvulsantRecoveredSenapati, et al [60] IndiaCase report222MVomiting, disorientationCT, MRIYes>1Left parieto-occipitalN/AN/ASurgical removal [Dowling]NoneCyst wall punctureNoneN/ARecovered40MSeizure, headache, vomiting, right side hemiparesisCTYes1Left fronto-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneN/ARecoveredImperato et al [61]ItalyCase report19MHeadache, diplopiaCT, MRIYes1Right temporo-parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredRamosaço et al [62]AlbaniaCase report122FHeadache, vomiting, seizureMRIYes6 Left frontal lobe, left frontal-parietal, left temporo-parietal, right occipital and right frontal1st:2.792nd:4.183rd:4.294th:2.89 5th:4.09 6th:2.84PositiveSurgical removalNoneNoneNoneAlbendazole, AntiepilepticEncephalomalaciaRavanbakhsh et al [63]IranCase report112MVision disturbanceMRIYes1Left parietal8N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/APulavarty [64]IndiaCase report116FGeneralized seizureCTYes1Left fronto-temporal4.89N/ASurgical removal [Dowling]NoneRupture of cystNoneAlbendazoleRecoveredShastry et al. [65]IranCase report17FBlurred visionCTYes1Left parieto-temporal5.65N/Asurgical removal [Dowling]NoneNoneNoneN/AN/AChen et al [66]ChinaCase report128FSeizureMRIYes1Right frontalN/APositiveConservative [Albendazole]N/AN/AN/ANoneSize of the cyst reducedKaushik et al [67]IndiaCase report153MSeizure exacerbationCTYes>1Right parieto-occipitalN/AN/ASurgical removalNoneNoneNoneAlbendazoleN/AWani, et al [68]IndiaCase report113MGeneralized seizure, vomitingContrast CTYes1Right occipital8.48N/ASurgical removalNoneNoneNoneN/ARecoveredArmanfar et al [69]IranCase report146FHeadache, blurred visionCT, MRIYes>1Right parieto-occipitalN/AN/ASurgical removalNoneRupture of cystNoneAlbendazoleRecoveredKhan et al [70]PakistanCase report18MHeadache, fever, vomitingContrast MRIYes19Right frontalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazole, Steroid, Antibiotic, AntiepilepticRecoveredCharles et al [71]CongoCase report132N/ASeizure, vomitingContrast CTYes2Bilateral hemisphere, right temporo-parietal1st:1.02 2nd:6.87N/ASurgical removal [Arana]NoneNoneNoneAlbendazole, SteroidImprovedGarg et al. [72]IndiaCase report147MHeadache, vomitingMRIYes7 Both sides of cerebrumN/APositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleDisturbed verbal outputAbuhajar et al [73]LibyaCase report150MHeadache, left side numbness, left toes paresthesia, vomitingContrast CT, MRIYes3 Right temporo-parietal1st: 3.5 2nd: 3.83rd: 4.0N/ASurgical removalN/AN/AN/AN/AN/AUmerani et al. [74]PakistanCase report122FHeadacheCT, MRIYes1Right temporo-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredTouzani et al. [75]MoroccoCase report15MVomiting , weakness, seizureCTYes1Left fronto-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedKibzai et al [76]PakistanCase series310MLeft side paresthesia, nauseaCT, contrast MRIYes1Right temporo-parietalN/AN/ASurgical removal [Dowling]NonePuncture of CystNoneAlbendazole, AntiepilepticRecurrence40MVomiting, altered behaviorCT, MRIYes1Left parieto-occipitalN/AN/ASurgical removal [Dowling]NoneRupture of cystNoneAlbendazoleRecovered72MSeizure, personality disorderCT, MRIYes32Right frontalN/AN/ASurgical removalNoneNoneNoneAlbendazoleImprovedDuransoy et al [77]TurkeyCase report113MHeadache, nausea, vomitingCTYes1Right temporo-parietal10N/ASurgical removal [Arana]NoneNoneLeft hemiparesis, subdural hygromaAlbendazoleImprovedQureshi et al [78]PakistanCase report111MSeizureMRIYes1Left posterior-parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneN/AN/ASenol et al. [79]TurkeyCase report16FHeadache with photophobia and phonophobiaMRIYes1Right frontotemporal10.5NegativeSurgical removal [Dowling]NoneNoneNoneAlbendazole, AntiepilepticRecoveredKandemirli et al [80]TurkeyCase report16MNausea, vomitingCTYes1Right frontal extended to lateral ventricle7.95N/ASurgical removal [Dowling]NoneNoneNoneAlbendazole, AntiepilepticRecoveredBahannanet al [81]YemenCase report117MImbalance, ataxia, falls, right side hemiparesis, fever, headache, decreased visual acuity, diplopia.CTYes1Right fronto-parietal5N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredKumar et al [82]IndiaCase report125MHeadache, vomiting, right side weakness, seizureContrast CT, MRIYes1Left parietalN/AN/ASurgical removalNoneNoneNoneN/AN/AAgrawal et al [83]IndiaCase report125MDifficulty walking, seizureCT, contrast MRIYes1Left fronto-parietal24.63N/ASurgical removalNoneNoneNoneAlbendazoleN/AMustafa et al [84]IraqCase report12MFocal seizureCTYes1Left parietal6N/ASurgical removal [Dowling]NoneNoneNonenoneRecoveredIJaz et al [85]PakistanCase report18MHeadache, fever, right-side hemiparesis, difficult walkingCTYes1Left cerebrum8.94N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredBorni et al [86]TunisiaCase report15MHeadache, vomitingCT, contrast MRIYes2 Left occipital1st: 3.39 2nd: 2.25PositiveSurgical removalNonePuncture of CystNoneAlbendazoleRecoveredKojundzicet al [87]CroatiaCase report134FHeadache, vomitingCT, MRIYes3 Right temporo-parietal1st:3.82nd:2.93rd: N/APositiveSurgical removalNoneNoneOsteomyelitisAlbendazoleImprovedSiyadatpanah et al [88]USACase report139MRight side paresthesia, imbalanceMRIYes1Left fronto-parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecoveredAkrim et al [89]MoroccoCase report122FHeadache, vomiting, blurred visionCTYes>1Left parieto-occipitalN/AN/ASurgical removal [Arana]NoneNoneNeurological deficitAlbendazoleImprovedZeynal et al[90]TurkeyRetrospective cohort 1250MHeadache, left side hemiparesisCT, MRIYes1Right parietalN/AN/ASurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 455MDysarthria, focal seizureCT, MRIYes1Left temporo-parietalN/AN/ASurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 540MHeadache, nausea, vomitingCT, MRIYes1Left parietalN/AN/ASurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 426MHeadache, left side hemiparesisCT, MRIYes1Left parietalN/AN/ASurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 535FHeadache, right side hemiparesisCT, MRIYes1Left thalamusN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 525MRight side hemiparesisCT, MRIYes1Left thalamusN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 464MDysphasiaCT, MRIYes1Right temporalN/APositiveSurgical removalN/AN/AN/AAlbendazoleDeath27FHeadache, nausea, vomiting, altered consciousnessCT, MRIYes1Left parietalN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 513MRight side hemiparesisCT, MRIYes1Left parieto-occipitalN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 562MLeft side hemiparesisCT, MRIYes1Right fronto-parietalN/APositiveSurgical removalN/AN/AN/AAlbendazoleDeath49MHeadacheCT, MRIYes1Right parieto-occipitalN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 552MHeadacheCT, MRIYes2 Left temporal, right frontalN/APositiveSurgical removalN/AN/AN/AAlbendazoleGlasgow outcome: 5Ozdol et al [91]CroatiaCase report123MNausea, imbalance, headache, urinary and fecal incontinenceMRINo1Left cerebellum2.08PositiveSurgical removalNoneNoneNoneAlbendazoleRecoveredMa et al [92] ChinaCase report250MHeadache, nausea, vomitingContrast CT, contrast MRIYes2 Right frontal, left temporalN/AN/ASurgical removalNoneNoneNoneAlbendazoleRecovered42FHeadache, vomitingContrast CT, contrast MRIYes2 Left frontal, left temporalN/AN/ASurgical removalNoneNoneNoneAlbendazoleRecoveredMokhtari et al [93]IranCase report160FHeadache, bilateral decreased vision, delusions, cognitive disordersContrast CT, MRIYes2 Left fronto-parietal, right parieto-occipital1st: 32nd: 2.08N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredBenzagmout et al [94] Morrocco Case report221FSeizureContrast CT, contrast MRIYes1Right frontalN/AN/ASurgical removalNoneNoneNoneAntiepilepticRecovered24FHeadache, vomitingCTNo1Right frontal4.47N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredRay et al [95]IndiaCase report14MHeadache, nausea, vomiting, altered sensorium, feverCTYes>1Left fronto-parietalN/ANegativeSurgical removal [ Dowling]N/AN/AMeningitis, subdural effusion, hydrocephalusN/ARecoveredYiş et al [96]TurkeyCase report17MHeadache, vomiting, myalgia, abdominal painMRIYes1Temporo-parieto-occipital8N/ASurgical removal [ Dowling]NoneNoneNoneMebendazoleRecoveredPer et al [97] TurkeyCase series 515MHeadache, intellectual impairment, dysphasiaCTYes4 Left fronto-parietal , left occipitalN/AN/ASurgical removal [ Dowling]NoneNoneNoneN/ARecurrence & Death15MHeadache, faintness, diplopia, vomitingCT, MRIYes1Right temporo-parietalN/AN/ASurgical removal [ Dowling]NoneNoneNoneAlbendazoleRecovered4FHeadache, nausea, vomiting, seizureCTYes1Right parietalN/AN/ASurgical removal [ Dowling]NoneNoneNoneAlbendazoleRecurrence16MVomiting , seizure, headacheMRIYes1Right parietalN/AN/ASurgical removal [ Dowling]NoneNoneNoneAlbendazoleRecovered11MHeadache, vomiting, strabismusMRIYes>1Right occipital,right parietalN/AN/ASurgical removal [ Dowling]/neuronavigationNoneNoneNoneN/AImprovedRadmenesh et al [98]IranCase report27FHeadache,vomiting, right side hemiparesisCTYes4 Left frontalN/ANegativeSurgical removalNoneNoneHydrocephalusAlbendazoleRecovered12MHeadache,vomitingCTYes1Right fronto-temporalN/ANegativeSurgical removalNoneNoneNoneAlbendazoleRecoveredBalak et al [99]TurkeyCase report116MHeadache, visual disturbanceCT, MRIYes1Right parieto-occipital6PositiveSurgical removal/microsurgeryNoneNoneNoneAlbendazoleRecoveredNajjar et al [100]Saudi ArabiaCase report111MLeft side hemiparesisCT, contrast MRIYes1Right hemisphere8NegativeBurr-hole surgical removalNonePuncture of CystAbscess at surgical siteAlbendazoleRecoveredTatli et al [101]TurkeyCase report37MHeadache, left side hypoesthesiaCT, MRIYes1Right parietal7.65N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleRecovered15FHeadache, vomitingCTYes1Left fronto-parietal8.48N/ASurgical removal [Dowling]NoneRupture of cystNoneAlbendazoleRecovered10FHeadache, vomiting, left side weaknessCT, MRIYes1Right fronto-temporo-parieto-occipital10.32N/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleN/AYurt et al [102]TurkeyCase report119FHeadache, vomiting, seizureCT, MRIYes>1Bilateral hemispheresN/ANegativeMultiple surgeriesLeft side hemiplegia, deteriorationNoneRecurrence of symptomsAlbendazoleRecurrenceAydin et al[103]TurkeyCase report17MHeadache,behavioral disturbance, counting and calculation disorders, mental regressionCTYes1Left temporo-parietal7.48PositiveSurgical removalNoneNoneLeft hemiparesisMebendazoleRecoveredTuzun et al[104]TurkeyCase series139MHeadache, seizureCT, MRIYes1Left parieto-occipitalN/AN/ASurgical removal [Dowling]DeteriorationNoneSubdural effusionAlbendazoleImproved5MRight side hemiparesisCT, MRIYes1Left parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNonePorencephalic cystAlbendazoleImproved16FHeadache, nausea, vomitingCT, MRIYes1Right parieto-occipitalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImproved11FHeadache, nausea, vomitingCT, MRIYes1Left temporo-parietalN/AN/ASurgical removal [Dowling]NoneNoneCerebral spinal fluid collectionAlbendazoleImproved12MLeft side hemiparesis, seizureCT, MRIYes1Right frontalN/AN/ASurgical removal [Dowling]DeteriorationNoneSubdural effusionAlbendazoleImproved8FHeadache, loss of consciousnessCT, MRIYes1Left fronto-parietalN/AN/ASurgical removal [Dowling]DeteriorationNoneNoneAlbendazoleImproved3MRight side hemiparesisCT, MRIYes1Left parietalN/AN/ASurgical removal [Dowling]DeteriorationNoneSubdural effusionAlbendazoleImproved17MHeadache, left side hemiparesisCT, MRIYes1Right parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImproved18MHeadache, right side hemiparesisCT, MRIYes1Left fronto-parietalN/AN/ASurgical removal [Dowling]NoneNoneHemorrhageAlbendazoleImproved16FRight side hemiparesisCT, MRIYes>1Left occipital, left parietalN/AN/ASurgical removal [Dowling]NoneRupture of cystNoneAlbendazoleRecurrence11MHeadacheCT, MRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImproved9FHeadache, nausea, vomitingCT, MRIYes1Right occipitalN/AN/ASurgical removal [Dowling]NoneNoneHemorrhageAlbendazoleImproved5FHeadache, right side hemiparesisCT, MRIYes1Left parietalN/AN/ASurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedBakaris et al [105]TurkeyCase report18FRight upper paresis, headacheCTYes1Left temporo-parieto-occipital8.14N/ASurgical removalNoneNoneNoneAlbendazoleRecoveredGuney et al [106]TurkeyCase report118MHeadache, neck painCTYes1Left fronto-parietalN/APositiveSurgical removalNoneNoneNoneN/AN/AÖnal et al [107]TurkeyCase report17FAtaxia, apraxia, Headache, tremorCT, MRIYes1Right temporo-parietal6.21N/ASurgical removal [Dowling]NoneNoneNoneN/ARecoveredMuthusubramanian et al [108]IndiaCase report140FHeadache, right side hemiparesis, double vision, gait abnormalityContrast CTYes1PonsN/AN/ASurgical removalNoneNoneNoneN/AImprovedKabatas et al [109]TurkeyCase report126FHeadache, nausea, vomiting, seizureMRIYes1Left frontal4.13PositiveSurgical removal [Dowling]NoneNoneNoneAlbendazoleImprovedMenkü et al [110]TurkeyCase report135MSeizureCT, MRINo1Righ parieto-occipital4.74NegativeSurgical removalNoneNoneNoneN/ARecoveredAnvari et al [111]IranCase report15FHeadache, nausea, vomitingContrast CTNo1Right fronto-parietalN/AN/ABurr-hole surgical removalNoneNoneNoneAlbendazoleRecoveredKaradag˘et al [112]TurkeyCase report145FSeizure, confusionCTYes2Left fronto-parietal, right parietal5NegativeSurgical removalDeteriorationPuncture of the left cystNoneAlbendazoleRecurrenceCT; computed tomography, MRI; magnetic resonance imaging, ISHC; Imaging suggested hydatid cyst, N/A; non-available, OP; operative,*Improved = Symptomatic improvement but not complete recovery during the follow-up period. Recovered = Complete recovery/free of symptoms.Table 2. Baseline characteristics of the study and the participants.VariablesFrequency/Percentage Country of study Turkey Iran India Morocco Iraq Pakistan Croatia Others 27 (24.1%)19 (16.7%)17 (15.2%)11 (9.8%)5 (4.6%)5 (4.6%)3 (2.7%)25 (22.3%) Study design Case Report Case Series Retrospective cohort 101 (90.2%)10 (8.9%) 1 (0.9%) Age, year, mean [SD]20.44± 16.76 Age group ≤9 10-19 20-29 30-39 40-49 50-59 60-69 70-79 80-89 52 (29.2%)62 (34.8%)24 (13.5%)12 (6.7%)12 (6.7%)10 (5.6%)3 (1.7%)1 (0.6%)2 (1.1%) Gender Male Female N/A 107 (60.1%)68 (38.2%)3 (1.7%) Residency Rural Urban N/A 71 (39.9%)8 (4.5%)99 (55.6%) Previous history of hydatid disease Yes No N/A 13 (7.3%)161 (90.5%)4 (2.2%) Type of hydatid disease Cystic Alveolar 158 (88.8%)20 (11.2%) Presentation Symptomatic Asymptomatic 168 (94.4%)10 (5.6%) Presenting complaintHeadacheVomitingNauseaSeizureParesisImpaired vision Impaired conscious levelSpeech abnormalities *FeverAltered sensorium **Psychological disturbanceOther symptoms 112 (62.9%)77 (43.3%)35 (19.7%)54 (30.3%)51 (28.7%)23 (13%)12 (6.7%)10 (5.6%)8 (4.5%)8 (4.5%)7 (4.0%)31 (17.4%) Duration of presenting symptoms [mean]19 weeks Multiple organ involvement Yes No N/A 48 (27%)128 (71.9%)2 (1.1%) Site of the cyst/lesion [s] Left-side multi-lobe involvement Right-side multi-lobe involvement Bilateral multi-lobe involvement Frontal lobe Parietal lobe Temporal lobe Occipital lobe Left Hemisphere [unspecified location] Right Hemisphere [unspecified location] Other [Cerebellum, Thalamus, Pons] 50 (28.1%)47 (26.4%)11 (6.2%)17 (9.6%)33 (18.5%)5 (2.8%)4 (2.2%)2 (1.1%)2 (1.1%)7 (4%) Disease status per number of cysts/lesions Primary-solitary Primary-multiple Secondary-solitary Secondary-multiple 118 (66.3%)27 (15.1%)23 (13%)10 (5.6%) Neurological+/-other physical examination Normal Positive findings N/A 30 (16.8%)92 (51.7%)56 (31.5%) CT/MRI Findings Suggesting hydatid disease Not suggesting hydatid disease 170 (95.5%)8 (4.5%) Serology PositiveNegative N/A 34 (19.1%)21 (11.8%)123 (69.1%) Type of managementConservativeSurgical/Open ***Burr-hole 5 (2.8%)170 (95.5%)3 (1.7%) Disease outcomeDeathSurvivedN/A 6 (3.4%)139 (78.1%)33 (18.5%) Recurrence Recurrence alive Recurrence dead 11 (6.2%)2 (1.1%) * Speech abnormalities: aphasia, apraxia of speech, dysphonia, slurred speech, and others. **Altered sensorium: paresthesia, numbness, and heaviness.*** Surgical removal by (Dowling technique, modified Arana-Inguinz technique, surgical removal under neuronavigation, and microsurgery). DiscussionThe World Health Organization (WHO) has categorized human echinococcosis under the umbrella of tropical neglected diseases (TNDs) that require control, as the disease remains a significant health issue in endemic regions [1]. Domestic dogs serve as the primary definitive hosts for both species of Echinococcus and pose the highest risk of transmitting cystic and alveolar echinococcosis to humans. Infection in dogs occurs when they consume livestock offal containing hydatid cysts, after which they release parasite eggs in their feces, contaminating soil, water, and grazing fields. Livestock acquire the infection by ingesting these eggs during grazing, while humans are most often infected through eating or drinking contaminated food or water [114,115].In this systematic review, studies on two genera of clinical interest, Echinococcus granulosus and Echinococcus multilocularis, have been reviewed. Several mechanisms have been proposed for the migration of Echinococcus larvae to the brain. Larvae hatching from ingested eggs in the intestine enter the portal circulation, spreading to different tissues where they develop hydatid disease. Two barriers can protect against CNS involvement: the first is the liver through portal circulation, and the second is the lung, which may act as a secondary filter. The lack of these effective sieves, problems in the immune system, special architecture of brain tissue, disrupted capillaries in the lungs, and structural heart diseases such as patent ductus arteriosus and patent foramen ovale may all provide a gateway to the brain [10,11]. This disease commonly affects supratentorial regions of the brain, specifically within the distribution of the middle cerebral artery, primarily targeting the parietal and frontal lobes [77,78,107]. Generally, BHD is classified as “primary” or “secondary”. The primary disease is rare; it results from direct infestation of the brain without the involvement of other organs. It most often presents as a solitary, spherical, and unilocular cyst surrounded by a broad capsule, which usually contains protoscoleces and renders a fertile lesion. The secondary type is typically characterized by multiple cerebral cysts that result from the rupture of a cyst in other organs. They lack brood capsules and protoscoleces, rendering them infertile. Therefore, the risk of recurrence after their rupture is negligible. However, on rare occasions, multiple primary cysts can occur within the brain parenchyma due to multiple larval intakes in patients with defective immune systems, metastatic deposits from the rupture of a primary cyst in the brain, or the presence of cardiac anomalies. On the other hand, alveolar disease tends to result in multiple intracerebral lesions and might resemble and behave as a malignant lesion [90-93]. Cerebral HD is considered a childhood disease, most commonly (50–75%) seen in children and young adults. Additionally, patients with cerebral HDs may also have concomitant cysts in other organs, although this occurs in less than 20% of patients with intraparenchymal hydatidosis [5,6,105]. In this systematic review, most of the cases (64%) were affected during their first and second decades of life. Multiple cysts or lesions were present in about 21% of the cases. Among these, 15.1% were primary multiple diseases, while only 5.6% of the cases had secondary multiple hydatidosis. Thus, the findings of this review disagree with the assumption that primary multiple BHD is rarer than secondary multiple lesions. Additionally, 48 cases (27%) had concomitant disease in other organs.Signs of raised intracranial pressure (headache, nausea, vomiting) and focal neurological deficits are the most common presentations of the disease. Seizures, visual disturbances, and cranial nerve involvement are also common presenting complaints reported in the literature [103,104]. In this study, headache was the most common presenting symptom (62.9%), followed by vomiting (43.3%), similar to the other reported studies. Seizure, paresis, nausea, and visual disturbance were reported in 30.3%, 28.7%, 19.7%, and 13% of the cases, respectively. The mean duration of symptoms at the time of presentation was 19 weeks.Timely diagnosis of BHDs is crucial because failure to make a prompt diagnosis could result in fatal consequences. Moreover, handling the cystic or mass lesion during surgical intervention is essential for reducing intraoperative complications and preventing disease recurrence. It has been declared that serological testing for the diagnosis of HD is of limited accuracy. Therefore, it is not sufficient on its own to confirm the diagnosis of HD [104]. Imaging modalities are the mainstay of diagnosis in patients with suggestive history and clinical findings, even when serological tests are negative. The disease generally poses common characteristics and pathognomonic features on scanners. Typically, CT and MRI are the primary imaging techniques, which can often be sufficient to achieve a diagnosis. For BHD, the main appearance on CT is a round, intra-parenchymal, usually large cystic lesion with a well-defined border. The cyst fluid is typically isodense or slightly hyperdense compared to cerebrospinal fluid. Calcifications or septations may or may not be present. Calcifications are primarily peri-cystic, giving a 'ground-glass' appearance, suggesting infection or damage before the larva's death. The MRI scans show a thin-walled spherical cyst containing fluid with cerebrospinal fluid characteristics on all sequences. Rim wall contrast enhancement and peripheral edema are much less common in hydatid cysts, and when present, may suggest other radiological differential diagnoses. The presence of multiple small daughter endocysts, characteristic of cystic echinococcosis, is the key distinguishing feature from other cystic lesions in the brain [1-4]. There are a few reports on the CT and MRI appearance of cerebral AE. The lesions may appear as solid, semisolid, or lobulated cystic or mass lesions with definite margins. Calcifications are usually scattered throughout the lesion, unlike in CE, where they are mainly confined to the pericystic region. Predominant features include surrounding edema and various types of contrast enhancement, such as peripheral ring-like, heterogeneous, nodular, and cauliflower-like patterns, indicating an inflammatory reaction around the lesion. Diffusion-weighted MRI is useful in distinguishing lesions from edema. Therefore, the diagnosis should be based on evidence of a primary focus in another location, an appropriate clinical history, the prevalence of the infection in the host's geographic location, and laboratory findings, as a standard practice for diagnosing and differentiating cerebral AE [90-94]. Following laboratory tests and imaging, a histopathological examination confirms the final diagnosis [80,97]. Regarding the findings of this systematic review, a serology test was performed in 30.9% of the studies, and it was positive in 19.1% of the cases. Although this study could not statistically confirm the exact role of serology in detecting BHD, the data suggest that serology alone cannot be relied upon for diagnosing cerebral HD. Additionally, imaging modalities, including both CT and MRI, were indicated for the diagnosis of the disease in 95.5% of cases. The management of BHD typically involves a combination of surgical and adjunctive medical therapies. The treatment plan may vary depending on the size, number, location, and depth of invasion of the lesions into the brain parenchyma. Consequently, the prognosis of the disease can vary based on these factors. The most effective method is surgery. Although different surgical techniques have been investigated, there is consensus that intact cyst removal and total resection of the mass lesion without rupturing it or spilling its contents should be the core of the surgery. This approach is crucial in preventing perioperative complications, recurrence, and progression of the disease. The Dowling-Orlando technique, later modified by Arana-Iniguez and San Julian, is the most widely used surgical method for removing CNS hydatid cysts. This technique involves the formation of a hydrostatic assistant and continuous irrigation with hypertonic saline to dissect the cyst wall from the brain parenchyma, thereby achieving the intact removal of the cyst [26,42,53]. The location of the cyst, its size, adhesion to surrounding structures, multiplicity, and the presence of deep-seated lesions, especially in cases of alveolar E. multilocularis, can make the removal of the cyst intact challenging. The Dowling-Orlando technique may not be feasible in all cases of brain HD. In such situations, alternative methods aimed at minimizing the spillage of the cyst contents can be considered. The PAIR technique, which involves puncture and needle aspiration of the cyst, followed by the injection of a scolicidal solution for 20-30 minutes and cyst re-aspiration, has been reported as a reasonable approach [74,75,111].Furthermore, the technique of burr-hole opening over the site of the cyst and the introduction of a cannula through the brain to drain the cyst, followed by removal of the cyst wall, has also been reported. However, this method of aspiration is discouraged unless total removal by other techniques is impossible. In patients with brain AE, radical excision should be performed for all accessible lesions. These procedures can be combined with the use of microsurgical and neuronavigation modalities to reduce perioperative complications [56,104]. Intraoperative cyst rupture is a common and serious event. Spillage of the cyst content into the brain tissue may lead to a fatal anaphylactic reaction, which is a chief cause of mortality during surgery. Furthermore, it increases the risk of high recurrence rates of the disease, particularly if the cyst is primary, as it is a fertile lesion [33,35]. The main reported early post-operative complications often arise due to the space left after the excision of large lesions. These may include subdural hematomas, hyperpyrexia, cerebral edema, cortical collapse, or even cardiorespiratory failure. Late post-operative complications such as porencephalic cyst, hydrocephalus, pneumocephalus, hemorrhage, seizures, and focal neurological deficits can occur in the days following surgery. These complications may require conservative management or further intervention [11,20,33]. Although the principal treatment of HD is surgery, pre-and post-operative adjunctive anthelmintic therapy, mainly with albendazole, may be considered. Albendazole can sterilize the cysts, decrease the tension in the cyst wall (thus reducing the risk of spillage during surgery and subsequently the risk of anaphylaxis and recurrence), and is also used for inoperable lesions. The optimal duration of treatment is still unclear, but recommended regimens involve albendazole taken orally at 10–15 mg/kg/day for 3–6 months, followed by a 'rest period' of 15 days after each month. Supportive medications can also be used to manage the presenting symptoms associated with the disease [12,93]. Among the several reviewed studies, a history of traumatic cyst rupture or iatrogenic cyst puncture during surgical procedures played a role in causing the recurrence of the disease [14,76,97]. In the present study, the primary treatment was surgical intervention in most cases (97.2%). The surgical approaches were commonly Dowling-Orlando or modified Arana-Iniguez (95.5%), while three cases (1.7%) underwent burr-hole surgery. In addition, five cases (2.8%) had been managed with conservative treatment only. The recurrence was reported in 13 cases (7.3%). Among them, six cases had intraoperative rupture of the cyst, and two had iatrogenic puncture of the cyst. No alveolar cases showed a recurrence. For this reason, this study recommends surgical intervention over conservative treatment. Follow-up for up to two years is recommended, especially in cases of giant hydatid disease or perioperative complications. In this systematic review, the mean follow-up period was 12 months. It has been reported that the majority of BHD cases can recover and survive with proper management [11,20]. Accordingly, the mortality rate in this study was only 3.4%. The major limitation of this study is the predominantly descriptive nature of the included studies, which may not yield reliable outcomes and can introduce bias. Further research employing rigorous study designs, such as trials comparing different surgical techniques for managing BHD, is recommended, particularly for the alveolar form.ConclusionImaging modalities, such as CT and MRI, are the primary diagnostic tools for intra-parenchymal BHD, while serological tests alone are not reliable. Surgical intervention remains the definitive treatment for BHD. However, clinical diagnosis and treatment of AE continue to pose significant challenges. Therefore, in endemic regions, early diagnosis and treatment are crucial for improving prognosis. A history of cyst rupture during surgery may increase the risk of recurrence, necessitating extensive follow-up.DeclarationsConflicts of interest: The authors have no conflicts of interest to disclose.Ethical approval: Not applicable.Patient consent (participation and publication): Not applicable.Funding: The present study received no financial support.Acknowledgements: None to be declared.Authors' contributions: FHF and ASH were significant contributors to the conception of the study and the literature search for related studies. HOA and ABL involved in the literature review, study design, and manuscript writing. ZOKA, KAA, RJR, AKG, SMA, and ADA were involved in the literature review, the study's design, the critical revision of the manuscript, and data collection. FHF and HOA confirm the authenticity of all the raw data. All authors approved the final version of the manuscript.Use of AI: ChatGPT-4.0 was used to assist in language editing and improving the clarity of the manuscript. All content was reviewed and verified by the authors. Authors are fully responsible for the entire content of their manuscript.Data availability statement: Not applicable.